Research paper efficacy and safety of telitacicept combined with standard therapy for lupus nephritis: a single-center real-world study - Liu, Xiaoxia; Li, Na; Wu, Pengjia; Qin, Longyan; Fan, Youyang; Liu, Jun; Zhang, Aifei; Yang, Lei; Tian, Ting; Zeng, Jiashun (Frontiers in Immunology, 2025)
BackgroundLupus nephritis (LN) is a severe complication of systemic lupus erythematosus with suboptimal response to standard therapy. This study evaluated the efficacy and safety of telitacicept, a novel fusion protein targeting both BLyS and APRIL, combined with standard therapy in patients with active LN.MethodsThis retrospective study included 67 patients with biopsy-proven LN treated with telitacicept plus standard therapy between January 2022-July 2024. Primary endpoints included renal response rates, SRI-4, and safety at weeks 12, 24, and 52.FindingsComplete and partial renal response rates were 41.8%/26.9% at week 12 (n=67), 48.9%/34.0% at week 24 (n=47), and 56.3%/37.5% at week 52 (n=16). SRI-4 response rates increased from 55.2% at week 12 to 75.0% at week 52 (p=0.035 for trend). Proteinuria decreased significantly from 2.69g/24h at baseline to 0.51g/24h at week 24 (p<0.001). Median prednisone dose decreased from 40mg at baseline to 7.5mg at week 52 (p<0.001). Thirteen adverse events occurred with no serious events reported.InterpretationTelitacicept combined with standard therapy demonstrated significant efficacy in LN with an acceptable safety profile, achieving high response rates, reduced proteinuria, improved immunological parameters, and substantial glucocorticoid-sparing effects.